2020
DOI: 10.1021/acs.jafc.9b06452
|View full text |Cite
|
Sign up to set email alerts
|

Quantifying Dicamba Volatility under Field Conditions: Part II, Comparative Analysis of 23 Dicamba Volatility Field Trials

Abstract: This study summarizes 23 field trials (over six geographic locations, with each trial composed of a separate field site and an application event) for quantifying the postapplication volatilization of dicamba from fields treated with an array of dicamba-containing formulations and tank adjuvants at an application rate of 0.56 or 1.12 kg dicamba acid equivalents (a.e.) per hectare (0.5 or 1.0 lb dicamba a.e. per acre). The data span 3 years of testing over a range of locations, field types, and environmental con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 30 publications
(48 reference statements)
0
29
0
1
Order By: Relevance
“…The two meta-analyses on dicamba volatility focused on visual injury and soybean yield (Egan et al 2014;Kniss 2018). Sall et al (2020) recently reported that no impact on plant height or soybean yield was detected after exposure to dicamba volatility in 23 field studies. The low-tunnel methodology used in the current study is a valuable tool to compare the effect of dicamba volatility on soybean.…”
Section: Low-tunnel Field Volatility Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…The two meta-analyses on dicamba volatility focused on visual injury and soybean yield (Egan et al 2014;Kniss 2018). Sall et al (2020) recently reported that no impact on plant height or soybean yield was detected after exposure to dicamba volatility in 23 field studies. The low-tunnel methodology used in the current study is a valuable tool to compare the effect of dicamba volatility on soybean.…”
Section: Low-tunnel Field Volatility Experimentsmentioning
confidence: 99%
“…Secondary dicamba movement via volatility is well documented (Behrens and Lueschen 1979;Egan et al 2014;Egan and Mortensen 2012;Jones et al 2019a;Sall et al 2020;Sciumbato et al 2004a;Soltani et al 2020) and may have been the culprit of some nontarget injury complaints over the 2017 through 2019 growing seasons. The seminal paper on dicamba volatility was published in 1979, reporting secondary movement from applications of dimethylamine (DMA) salt of dicamba in corn under field conditions in Minnesota (Behrens and Lueschen 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Although the sensitivity of these bioassays is more than adequate, a quantitative assessment via air sampling followed by chemical extraction and analysis may yield more direct indications of herbicide behavior (Mueller et al 2013;Mueller 2015). In a multi-state dicamba field flux study, dicamba OTM was reported at all locations, and up to 0.3% of applied dicamba was measured (Riter et al 2020;Sall et al 2020). There was no apparent relationship between recorded meteorological and soil conditions for each trial and the observed dicamba OTM.…”
Section: Introductionmentioning
confidence: 97%
“…Actuellement, il conviendra donc d'assumer la réduction de l'usage de ces molécules herbicides très efficaces dont l'utilisation est remise en cause par une partie de la population. Aux États-Unis, ce sont les dégâts liés à la volatilité du dicamba qui font fortement débat, du fait de son utilisation importante pour contrôler les adventices résistantes au glyphosate dans les PGM (Sall et al, 2020).…”
Section: Discussionunclassified